Disaster, Memory, and Maqāṣid: Rereading the Pharaoh Story in the Context of the Tragedy of Sumatera - Muzaqky Muthahhari; Lukmanul Hakim (ALSYS, 2026)
The flash floods and landslides in Aceh, North Sumatra, and West Sumatra demonstrate that hydrometeorological disasters are not solely natural phenomena but also cumulative consequences of upstream ecological degradation, including deforestation and peatland damage, compounded by governance failures. This study aims to analyze these disasters through a maqāṣidī interpretation of the Qur’anic story of Pharaoh to reveal the normative and political dimensions of leadership negligence. Employing a qualitative literature-based method, the study conducted hermeneutic analysis, thematic identification, and synthesis of primary and secondary sources concerning Qur’anic narratives, ecological conditions, and disaster policies. The findings reveal three principal points. First, “Pharaohistic” patterns of leadership, characterized by absolutism, the normalization of structural violence, and narrative manipulation, are reflected in political decisions that disregard public safety. Second, delays in declaring national disaster status aggravated emergency response and contributed to secondary fatalities by constraining the mobilization of resources and essential services. Third, effective disaster prevention and recovery require the integration of evidence-based ecological interventions, including upstream ecosystem restoration, a moratorium on land conversion, and peatland management, with policy reform, institutional accountability, and local community participation. The study concludes that disaster mitigation and reconstruction should be situated within the framework of maqāṣid al-sharīʿah, particularly ḥifẓ al-nafs, as a normative benchmark for governmental legitimacy and responsibility. Without structural ecological and governance reforms, similar disasters are likely to recur. These findings contribute to ecological Islamic studies by connecting Qur’anic narratives of oppressive leadership with contemporary disaster governance and imply the need for risk-based emergency declarations, upstream ecosystem rehabilitation, and transparent accountability mechanisms.